Students’ Accommodation and Academic Performance: the Case of Federal University Wukari, Nigeria - Abdulmudallib, Ibrahim; Luper, Anshula Kenneth (Darul Yasin Al Sys, 2024)
In response to growing concerns about the academic performance of higher education students, this study examines how accommodation choices influence academic outcomes at Federal University Wukari. By employing a mixed-methods approach, data was collected through surveys, interviews, and academic records. Results highlight a notable association between accommodation type and academic performance, with off-campus students exhibiting superior outcomes. To address these findings, recommendations are proposed, emphasizing the need to improve facilities, offer affordable housing options, and enhance safety measures to foster student success and well-being.